2022
DOI: 10.3346/jkms.2022.37.e332
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Intake and Risk of Hypertension: A Meta-Analysis of Cohort Studies

Abstract: Background It remains unclear whether coffee intake is associated with the risk of hypertension. This study aimed to investigate the association between coffee intake and the risk of hypertension by using a meta-analysis of cohort studies. Methods PubMed and Embase were searched using keywords in September 2022 to identify studies on coffee intake and the risk of hypertension. Results We included a total of 12 longitudinal cohort studies, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…There are several meta-analyses evaluating the relationship between coffee and HTN risk [12,51,52]. In the most recent meta-analysis, published in November 2022, 12 prospective cohort studies were included, and a null association was found [53]. However, this study has some methodological limitations.…”
Section: Discussionmentioning
confidence: 97%
“…There are several meta-analyses evaluating the relationship between coffee and HTN risk [12,51,52]. In the most recent meta-analysis, published in November 2022, 12 prospective cohort studies were included, and a null association was found [53]. However, this study has some methodological limitations.…”
Section: Discussionmentioning
confidence: 97%
“…There are currently conflicting results regarding coffee consumption and risk of hypertension. Three meta-analyses of prospective cohort studies found that high coffee consumption was not associated with increased blood pressure and in fact report a non-linear inverse dose-response relationship between coffee consumption and the risk of hypertension ( 33 35 ). On the other hand, a meta-analysis that included 11 randomized controlled trials (RCTs) with combined 470 study subjects (mean age 27 years), with a study duration ranging from 30 min to 4 weeks, found that caffeinated beverages (coffee and other caffeinated beverages) were associated with an overall short-term (within 4 weeks) blood pressure elevation of 3.04/2.45 mmHg.…”
Section: Effect Of Beverages On Health Outcomesmentioning
confidence: 99%
“…There are currently conflicting results regarding coffee consumption and risk of hypertension. Three meta-analyses of prospective cohort studies found that high coffee consumption was not associated with increased blood pressure and in fact report a non-linear inverse dose-response relationship between coffee consumption and the risk of hypertension (33)(34)(35). On the other hand, a meta-analysis that included 11 randomized controlled Average intake and among the group with very high consumption of added sugars (i.e.…”
Section: Hypertensionmentioning
confidence: 99%